Serum metabolites and hypercholesterolemia: insights from a two-sample Mendelian randomization study - Wang, Weitao; Qiao, Jingwen; Su, Zhaoyin; Wei, Hui; Wu, Jincan; Liu, Yatao; Lin, Rubing; Michael, Nerich (Frontiers in Cardiovascular Medicine, 2024)
Background Hypercholesterolemia, a major risk factor for cardiovascular diseases, lacks a comprehensive understanding of its association with serum metabolites in the pathogenesis. Methods This study employed genome-wide association study (GWAS) data to explore the relationship between serum metabolites and hypercholesterolemia, identifying significant metabolites through Mendelian Randomization (MR) and KEGG pathway enrichment analysis. Data on metabolites were sourced from a European population, with analysis focusing on individuals diagnosed with hypercholesterolemia. Results Out of 486 metabolites analyzed, ten showed significant associations with hypercholesterolemia, categorized into those enhancing risk and those with protective effects. Specifically, 2-methoxyacetaminophen sulfate and 1-oleoylglycerol (1-monoolein) were identified as risk-enhancing, with odds ratios (OR) of 1.545 (95% Confidence Interval [CI]: 1.230-1.939; P_FDR = 3E-04) and 1.462 (95% CI: 1.036-2.063; P_FDR = 0.037), respectively. On the protective side, 3-(cystein-S-yl)acetaminophen, hydroquinone sulfate, and 2-hydroxyacetaminophen sulfate demonstrated ORs of 0.793 (95% CI: 0.735-0.856; P_FDR = 6.18E-09), 0.641 (95% CI: 0.423-0.971; P_FDR = 0.042), and 0.607 (95% CI: 0.541-0.681; P_FDR = 5.39E-17), respectively. In addition, KEGG pathway enrichment analysis further revealed eight important pathways, including "biosynthesis of valine, leucine, and isoleucine", "phenylalanine metabolism", and "pyruvate metabolism", emphasizing their significant role in the pathogenesis of hypercholesterolemia. Conclusion This study highlights the potential causal relationship between specific serum metabolites and hypercholesterolemia, providing new insights into the metabolic underpinnings of the disease. The identified metabolites and pathways offer promising targets for therapeutic intervention and warrant further investigation.